Antenna array architecture - Mailloux, R.J. (Proceedings of the IEEE, 1992)
An abbreviated view of the topics included in modern array architecture is presented. The broad subject of architecture includes all the electromagnetic, thermal and mechanical aspects that need to be addressed by the array design team. The emphasis is on the interaction between the selection of an array aperture organization, corporate feeds, devices and elements, and a discussion of EHF monolithic array architecture is included as an example.< >